Early striatal amyloid deposition distinguishes Down syndrome and autosomal dominant Alzheimer's disease from late‐onset amyloid deposition. Issue 6 (22nd February 2018) - Cohen, Ann D.; McDade, Eric; Christian, Brad; Price, Julie; Mathis, Chester; Klunk, William; Handen, Benjamin L.
Abstract: Introduction: The objective of this study was to evaluate amyloid β (Aβ) deposition patterns in different groups of cerebral β amyloidosis: (1) nondemented with amyloid precursor protein overproduction (Down syndrome); (2) nondemented with abnormal processing of amyloid precursor protein (preclinical autosomal dominant Alzheimer disease); (3) presumed alteration in Aβ clearance with clinical symptoms (late‐onset AD); and (4) presumed alterations in Aβ clearance (preclinical AD). Methods: We performed whole‐brain voxelwise comparison of cerebral Aβ between 23 Down syndrome, 10 preclinical autosomal dominant Alzheimer disease, 17 late‐onset AD, and 16 preclinical AD subjects, using Pittsburgh Compound B–positron emission tomography. Results: We found both Down syndrome and preclinical autosomal dominant Alzheimer disease shared a distinct pattern of increased bilateral striatal and thalamic Aβ deposition compared to late‐onset AD and preclinical AD. Conclusion: Disorders associated with early‐life alterations in amyloid precursor protein production or processing are associated with a distinct pattern of early striatal fibrillary Aβ deposition before significant cognitive impairment. A better understanding of this unique pattern could identify important mechanisms of Aβ deposition and possibly important targets for early intervention.